Effect of Information Disclosures on the Performance of Public Hospitals in Embu County, Kenya (African Multidisciplinary Journal of Research, 2025)
Around the world, public hospitals perform better when information disclosures are in place. In Embu County, Kenya, public hospital performance was examined to see how information disclosure affects it. The study aimed to examine the effects of information disclosures on the performance of public hospitals in Embu County. Utilising operational efficiency and the level of satisfaction among healthcare workers and clients, public hospitals' performance was evaluated. The Diffusion of Innovation Theory was used to establish the theoretical framework for information disclosure and performance. The study had a target population of 350 consisting of 200 clients and 150 healthcare workers. The sample population was 140 comprising of 42.8%healthcare workers on duty that week and 57.2% of clients/patients admitted for at least two days in selected public hospitals. The distribution of healthcare workers is composed of 2.9% public hospital administrators, 2.9% clinical officers-incharge, 2.9% nurse-in-charge, 17.1% ordinary nurses, and 17.1% ordinary clinical officers. Utilizing the Statistical Package for Social Sciences (SPSS) version 24.0, descriptive statistics were used to evaluate quantitative data. The results of the descriptive statistics were presented as mean scores, frequencies, and percentages.MS Excel was used to draw graphs and charts. The major findings showed that 65% of healthcare workers agreed that HFCMs (Health Facility Committee Members) provided timely information disclosures to managers, administrators, clinical officers, and nurses. Further, 66.7% of healthcare workers were adequately satisfied that public hospital’s communication channels were effective. The study recommends that public hospitals should consider implementing more accessible, transparent, and reliable communication channels that foster both client and employee satisfaction; formulation of a policy that mandates standardized intervals for disclosures to relevant healthcare workers; HFMCs should seek to enhance the accuracy of the information shared with both healthcare workers and clients; and public hospitals should conduct regular audits of their information systems to ensure equal accessibility of healthcare services to all stakeholder and the public. In conclusion, this study will contribute to the growing body of information disclosure literature by offering study empirical evidence on the effect of timely, accurate, and well-structured communication on the performance of public hospitals in Kenya and globally. The insights obtained in the study highlight the critical role of effective disclosures in enhancing both client and employee satisfaction, thus fostering operational efficiency and organizational success.